Postural Evaluation of Vertebral Column in Children and Teenagers with Hearing Loss - Melo, Renato de Souza; da Silva, Polyanna Waleska Amorim; da Silva, Lícia Vasconcelos Carvalho; Toscano, Carla Fabiana da Silva (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Posture is determined by the performance of the visual, somatosensory and vestibular systems. Children with hearing loss can present problems in their posture or postural control, enabling postural deviations and alterations to appear in their vertebral column, possibly provoked by a hypoactivity of the vestibular system as a result of deafness.Objective: To evaluate the posture of the vertebral column in children and teenagers with hearing loss at school age, taking into consideration the sample gender and age.Method: A descriptive and prospective study was performed at both Duque de Caxias School and Rotary Rehabilitation and Special Education Center in Caruaru – Pernambuco. 44 students aged between 7-17 years old, out of whom 22 were female and 22 were male, with hearing loss were evaluated. The study was developed by way of a postural evaluation, using a symmetrograph, marking specific anatomical points with stickers placed over polystyrene balls and fixed with double-sided adhesive tape.Results: The results showed that all of the individuals evaluated in this study presented some kind of postural alteration in their vertebral column. Scoliosis was the most observed alteration among the students (84.1%), followed by thoracic hyperkyphosis (68.2%).Conclusion: It has been concluded that children and teenagers with hearing loss are exposed to postural alteration in their vertebral column. Such a condition can be associated with a number of factors comprising unfavorable ergonomics of the school environment, bad postural habits and impairment of the vestibular system by virtue of the hearing loss.
Keywords: evaluation; vertebral column; hearing loss; posture; deafness